Transactional distance in a blended learning environment - Jon Dron; Catharine Seidel; Gabrielle Litten (Association for Learning Technology, 2004)
This paper presents a case study that describes and discusses the problems encountered during the design and implementation of a blended learning course, largely taught online through a web-based learning environment. Based on Moore's theory of transactional distance, the course was explicitly designed to have dialogue at its heart. However, the reality of systemic behaviours caused by delivering such a course within a group of conventional further and higher educational institutions has led to an entirely unanticipated reversion to structure, with unpleasant consequences for both quality and quantity of dialogue. The paper looks at some of the reasons for this drift, and suggests that some of the disappointing results (in particular in terms of the quality of the students' experience and associated poor retention) can be attributed to the lack of dialogue, and consequent increase in transactional distance. It concludes with a description and evaluation of steps currently being taken to correct this behaviour.